Architectural Elements as A Component of Cultural Tourism: (Case Study: Cultural Heritage of Maospahit Gerenceng Temple) - Agusintadewi, Ni Ketut; Jyoti, Putu Savitri Dharma (University of Merdeka Malang, 2025)
Denpasar is a city in Bali that possesses a robust cultural heritage. One of the temples in Denpasar is the Maospahit Gerenceng Temple. The Maospahit Gerenceng Temple has been in existence for several centuries. The temple in question has been officially recognized by the Denpasar municipal government as a cultural tourist destination. The objective of this study was to identify architectural components within temple structures that possess potential as cultural tourist offerings, thereby contributing to the long-term viability of tourism in Bali. This descriptive qualitative analysis was conducted in the Maospahit Gerenceng Temple located in Denpasar, Bali. The data collection process involved employing participant observation to examine the traditional architecture of the Maospahit Temple, conducting in-depth interviews with the informant, Jero Mangku, and conducting a comprehensive review of relevant literature and documents. The results of the study indicate that the Maospahit Temple has distinctive architectural characteristics, particularly in its utilization of the Panca Mandala concept. The architectural design of this structure emerges from the process of acculturation between Balinese and East Javanese architectural styles, with the primary objective of enhancing the temple's role as a cultural tourist destination. Therefore, these distinctive architectural components serve as the primary focal point of the cultural tourism attraction of Maospahit Gerenceng Temple.